A novel low permittivity CaP2O6 microwave dielectric ceramics with low sintering temperature by B2O3-CuO additions - Ma, Pei Wen; Wang, Chang Hao; Yu, Zhen Fa; Zou, Rui; Zhou, Tao; Tan, Kar Ban; Zhou, Di (Elsevier, 2026)
Driven by 5 G to 6 G evolution, microwave dielectric ceramics with low relative permittivity (ε r ), high quality factor-frequency product (Q×f), and near-zero temperature coefficient of resonant frequency (τ f ) are in demand. In this study, single-phase CaP2O6 ceramics were synthesized via the solid-state reaction method, and their sintering properties were improved by adding 1 wt% B2O3-CuO. The pure CaP2O6 ceramic sintered at 900 ℃ exhibits ε r = 5.33, Q×f = 60,200 GHz, and τ f = − 43.9 ppm/℃. With B2O3-CuO additions, the ceramics sintered at 850 ℃, exhibiting ε r = 5.45, Q×f = 49,100 GHz, and τ f = − 52.1 ppm/℃. At 25–60 GHz, pure CaP2O6 ceramic exhibits ε r = 4.1 and Q = 1300–2200, and with the B2O3-CuO additions, the ε r increases to 4.5 and the Q decreases to 1000. The ceramics exhibit excellent compatibility with Cu electrodes, meeting low-temperature co-fired ceramic (LTCC) requirements for advanced microwave applications.